PENGARUH PEMBERIAN LARUTAN KOMBINASI MIKROMINERAL (Cu, Fe, Zn, Co), VITAMIN (A, B1, B12, C) DAN JUS BUAH MENGKUDU (Morinda citrifolia L.) SEBAGAI AIR MINUM TERHADAP KONSUMSI MINUM DAN BOBOT KARKAS PUYUH (Coturnix coturnix japonica L.). - Arumsari, Dina; Saraswati, Tyas Rini; Isdadiyanto, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2015)
Quail (Coturnix-coturnix japonica L.) was becoming more popular in Indonesia because of the product that produce was substantial enough like the meat and egg. This animal often used as an experiment in order to enhance it’s productivity. This research was to find out the potential of giving combination of micromineral (Cu, Fe, Zn, Co), vitamin (A, B1, B12, C) and morinda juice (Morinda citrifolia L.) solution as drinking water to drink consumption and weight of carcass. The treatment was begun when the quail was in age of 4 to 16 weeks. The experiment in this research was nonfactorial experimentation with complete random plan (RAL). The obtained data was analyzed by using the analysis of varian (ANOVA) and if there was a real difference then it will be done an advanced testing by using the Duncan test in confidence level 95%. According to the analysis result towards the drink consumption and the weight of carcass indicate any real difference inter cluster of quail whose it’s drink was added by combination of micromineral (Cu, Fe, Zn, Co), vitamin (A, B1, B12, C) and morinda juice with control, in conclusion that giving combination of micromineral (Cu, Fe, Zn, Co), vitamin (A, B1, B12, C) and morinda juice has the potency in the drinking management. Keywords : Coturnix coturnix japonica L., micromineral, vitamin, morinda juice